Copper (II) Oxide Nanoparticles as an Efficient Catalyst in the Azide–AlkyneCycloaddition. Issue 15 (22nd September 2016) - Amini, Mojtaba; Pourvahabi Anbari, Alireza; Ramezani, Sakine; Gautam, Sanjeev; Hwa Chae, Keun
Abstract: Copper (II) oxide nanorods and nanospheres were prepared and their structural, morphological, and electronic properties were investigated by X‐ray diffraction analysis, X‐ray absorption near edge structure, scanning electron microscope and transmission electron microscope.CuO nanoparticles efficiently catalyzes azide‐alkyne 1, 3‐dipolar cycloaddition (CuAAC) reaction producing corresponding 1, 2, 3‐triazole derivatives in excellent yields without use of any additives. The advantages of present protocol are mild reaction conditions, reusability of the catalyst, and applicability to a wide range of substrates. Abstract : Copper (II) oxide nanorods and nanosphereswere prepared and these nanoparticles has been utilized as a recyclable catalyst for the Huisgen 1, 3‐dipolar cycloaddition reaction.